2017
DOI: 10.1039/c7ra00790f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of aminothiazoles: polymer-supported approaches

Abstract: Aminothiazoles and their derivatives are of immense biological importance and have been consistently synthesized via various methods. However, the synthesis of aminothiazole derivatives has some problems such as poor yields, difficult isolation procedures, use of expensive catalysts etc. Recently, polymer or solid-supported synthetic protocols have attracted the attention from the research community because of their easy execution, increased product yields, greater selectivity, simple work-up procedures, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 112 publications
0
13
0
Order By: Relevance
“…The infrared spectra were `recorded on Shimadzu FT-IR spectrophotometer (Japan). 1 H NMR spectra were measured on a Bruker 400 MHz spectrometer (Turkey) in deuterated dimethyl sulfoxide (DMSO-d6) as a solvent and tetramethylsilane (TMS) as an internal standard. For in silico protein-ligand docking simulation, Mcule docking online.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The infrared spectra were `recorded on Shimadzu FT-IR spectrophotometer (Japan). 1 H NMR spectra were measured on a Bruker 400 MHz spectrometer (Turkey) in deuterated dimethyl sulfoxide (DMSO-d6) as a solvent and tetramethylsilane (TMS) as an internal standard. For in silico protein-ligand docking simulation, Mcule docking online.…”
Section: Methodsmentioning
confidence: 99%
“…The 2-aminothiazole agents are associated with a broad spectrum of biological properties, including anticonvulsant [1], antiviral [2], antimicrobial [3], antituberculous [4], antimalarial [5], anticancer [6], and hypertension [7], are just a few of the biological features related with 2-aminothiazole compounds. Cefdinir is a semi-synthetic broad-spectrum antibiotic 3 rd generation cephalosporin [8], and several marketed medicines for various diseases contain 2aminothiazole moieties as illustrated in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The available literature reveals that some research groups have reported polymer supported solid phase synthesis [36,37] as well as polymers as catalyst and catalyst support [38] for synthesis of bioactive heterocyclic compounds. In this review, for the first-time efforts are made to compile all the literature regarding the role of polymers for the improvements in the Friedlander quinoline synthesis.…”
Section: Scopementioning
confidence: 99%
“…There are many substituted thiazole-containing heterocycles covering a wide range of therapeutic targets including antimicrobial, anticancer, anti-inflammatory and anti-HIV. Aminothiazole scaffolds are important structural units in medicinal chemistry as they have shown antitumor [ 1 , 2 , 3 ], antiviral [ 4 , 5 , 6 ], antibacterial [ 7 , 8 , 9 ], anti-prion [ 10 ], psychotropic [ 11 ], anti-allergic [ 12 ], anti-hypertensive [ 13 ], anti-inflammatory [ 14 , 15 ], antifungal [ 16 ], antitubercular [ 17 , 18 ], anti-HIV [ 19 ], pesticidal [ 20 ], antiprotozoal [ 21 ], antipyretic [ 22 ], antioxidative [ 23 ] and analgesic activities [ 24 ]. Aminothiazole compounds act as ligands of estrogen receptors [ 25 ] and afford a new group of adenosine receptor antagonists [ 26 ].…”
Section: Introductionmentioning
confidence: 99%